Observações clínicas e laboratoriais em cães com cinomose nervosa - Tudury, Eduardo Alberto; Arias, Mônica Vicky Bahr; Bracarense, Ana Paula Frederico Loureiro; Megid, Jane [UNESP]; Dias Júnior, Rubens Ferreira (Universidade Federal de Santa Maria (UFSM), 1997)
Em 81 cães com sinais clínicos, lesões histológicas e corpúsculos de inclusão no sistema nervoso central característicos de cinomose nervosa foi constatada ocorrência freqüente de: alteração das reações posturais (87,65%), diminuição da secreção lacrimal (83,95%), presença de mioclonias (75,30%), paresias (69,12%), conjuntivite (56,79%), corioretinite/ hiperqueratose naso-digital (51,85%), linfopenia (51,85%), anemia (48,05%), principalmente microcítica hipocrômica, e discretas alterações liquóricas caracterizadas por aumento de proteínas totais (77,33%) e pleocitose linfocítica (50,72%). A presença de corpúsculos de Lenz em tecidos extraneurais oscilou entre 30 e 45 %, com maior freqüência em linfonodos. Enquanto outras anormalidades clínicas, neurológicas e laboratoriais não tiveram freqüência expressiva para dar apoio ao diagnóstico, o incorreto programa de vacinação foi uma constante.

Eighty-one dogs with clinical signs and histological lesions characteristic of distemper encephalomyelitis were evaluated. Only dogs with Lenz inclusion bodies in the central nervous system were included in the study. High prevalent findings included: changes in postural reactions (87.65%), decreased tear production (83.95%), myoclonus (75.30%), paresis (69.12%), conjunctivitis (56.79%), chorioretinitis/digital and nasal hyperkeratosis (51.85%). Anemia (48.05%), lymphopenia (51.95%), and mild changes in the cerebrospinal fluid characterized by increase in total protein (77.33%) and lymphocytic pleocytosis (50.72%) were common laboratorial findings. Presence of Lenz inclusions bodies in tissues other than nervous system varied from 30 to 45%, with a higher frequence in the limph nodes. Other abnormalities in physical, neurological and laboratorial examinations were not helpful in establishing the diagnosis. Most animals examined were not properly vaccinated.
Clinical and laboratory findings in dogs with distemper encephalomyelitis
Keywords: doenças dos cães; cinomose; sistema nervoso; diagnóstico; diseases of dogs; canine distemper; nervous system; diagnosis